Extended documentation for hand dermatitis patients: Pilot study on irritant exposures - Uter, Wolfgang; Bauer, Andrea; Bensefa-Colas, Lynda; Brans, Richard; Crepy, Marie-Noelle; Gimenez-Arnau, Ana; Filon, Francesca Larese; Hadzavdic, Suzana Ljubojevic; Pesonen, Maria; Schuttelaar, Marie L.; Wilkinson, Mark; Liden, Carola (Contact Dermatitis, 2018)
BACKGROUND: Irritant exposure may be a contributory cause or the sole cause of (occupational) hand dermatitis. However, the documentation of irritant exposures in clinical practice is not standardized. OBJECTIVES: To examine the feasibility and usefulness of a form with different items addressing both occupational and non-occupational irritant exposures in a semiquantitative way. METHODS: Between May 2016 and May 2017, successive patients with work-related hand dermatitis, irrespective of aetiology, were examined in 9 specialized European departments. Department-specific investigation was supplemented with the above proforma. The results were recorded by use of an anonymized secured online documentation system in a pilot study. RESULTS: Altogether, 193 patients were included; 114 females and 79 males, with a mean age of 40 years (range 18-68 years). The most common occupational group comprised healthcare workers (n = 35); occupational exposure of the hands to gloves, dusts and water without detergents of >2 hours/day was seen in 54.5%, 24.4% and 24.3% of patients, respectively. Non-occupational exposures rarely exceeded 2 hours/day. CONCLUSIONS: It is hoped that the set of descriptors will offer a basis for (clinical) epidemiological studies assessing the role of irritant exposures in occupational hand dermatitis, and to support a high level of quality and consistency in daily patient care.
EVALuna2:35664